COVID-19 Pandemic Management: Best Practices and Lessons From China, Japan and South Korea - Govindasamy, Geetha; Md Akhir, Md Nasrudin; Paidi, Rohayati (WILAYAH: The International Journal of East Asian Studies, 2021)
The management of COVID-19 pandemic is a reflection of how prepared states are when faced with a trans-boundary crisis. China, Japan and South Korea chose different strategies in containing the pandemic. All three were significantly successful in containing the pandemic in the initial stages. By using a qualitative approach, this article examines the timeline of events, measures are taken during the crisis to contain the coronavirus and the challenges faced in avoiding the further spread of the virus. The importance of early detection, defined procedures, the use of digital tools and possessing enough protective medical equipment and facilities are discussed at length. Since China, Japan and the Republic of Korea have been more successful in containing the virus compared to advanced economies, this research finds that the management practices of these East Asian countries inform policymakers in the future implementation of an infectious disease response strategy.